Risk of early onset pneumonia in neonates with abnormal gastric aspirate - IB. Mahendra; I Wayan Retayasa; I Made Kardana (Indonesian Pediatric Society, 2008)
Background Early onset neonatal pneumonia is the risk factorfor neonatal sepsis that increases risk for neonatal deaths.Recognition, prevention, and treatment of this problem is majorfactors in the managemant of high risk neonates. Analysis ofgastric aspirate, collected soon after birth is a useful screeningtest for predicting pneumonia.Objective To evaluate the risk of early onset of neonatalpneumonia in neonates with abnormal gastric aspirate.Methods A case control study was done on infants with earlyonset neonatal pneumonia born in Sanglah Hospital during theperiod of July 2004 until November 2005. The control groupconsisted of high risk infants without early onset pneumonia.Multiple logistic regressions was performed to determine theconfounding effects of multiple variables that were considered asrisk factors for early-onset neonatal pneumonia.Results Forty-five infants with early onset neonatal pneumoniawere recruited. Multivariate analysis showed that abnormal gastricaspirate and low APGAR score were significant factors associatedwith early-onset of neonatal pneumonia with OR 4.05 (95%CI1.26;13,02), P=0.019, and OR 6.95 (95%CI 2.45;19.77),P<0.0001, respectively.Conclusion Abnormal gastric aspirate and low APGAR score arerisk factors for early onset neonatal pneumonia in high risk infants.